ABDULLAH'S BLOGGING: A GENERATION 1.5 STUDENT ENTERS THE BLOGOSPHERE - Joel Bloch (Language Learning and Technology, 2007)
Blogging has emerged as one of the most popular forms of online discourse. The ease and lack of expense in setting up blogs has raised intriguing possibilities for language learning classrooms. The unique nature of their architecture and their low cost have not only affected how students can publish and distribute their work to a wider audience but also how they see themselves as authors. This paper focuses on the use of blogs in an L2 writing course concentrating on the controversies surrounding plagiarism. Blogs were used as a means of generating ideas for their academic papers and as texts that could be cited in their papers. This paper analyzes the blogs of a Somali immigrant student to explore blogs' relationship to the development of his academic writing. His purposes and strategies for using blogs are discussed both as a way of seeing the variety of writing strategies he developed in his blogs, as well as what his use of blogs could tell his teachers about the strengths and weaknesses of his writing. The paper attempts to improve our understanding of how blogging in L2 composition courses can contribute to the development of a student’s writing.